HUBUNGAN PENERAPAN PSAP NO 2 TENTANG LAPORAN REALISASI ANGGARAN DENGAN TINGKAT KINERJA DI DPPKAD KABUPATEN KUBU RAYAN (STUDI KASUS DI KABUPATEN KUBU RAYA ) - B51112007, Dimas Patria Akbar Widowo (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
The purpose of this study was to assess the implementation of Government Accounting Standards (PSAP) No. 2 in Kubu Raya and analyze the level of performance in DPPKAD Kubu Raya in accordance with the budget realization report that the implementation of the application PSAP No.2. Research using qualitative descriptive method. Data obtained through documentation and interviews. Results of research conducted through the application of some evaluation items PSAP No. 2 of Kubu Raya, the budget has provided information regarding the overall budget and is useful in evaluating the performance of the government, reports realization has also provided information that realization carried out in accordance with the budget. In other words, Achieving the performance of the organization in 2014 amounted to 94.04% while was very successful. budget management professional and accountable with reference to the PSAP No. 2 to the budget report Kubu Raya instrumental in helping the evaluation process to improve future performance levels Â  Keywords : Government Accounting Standards, Budget Realization Report, Level Performance, LAKIP (government performance accountability reports)